Safe commuting factors from existing guidelines in Malaysia: a review for the construction sector. (April 2018) - Sukor, E S A; Suratkon, A; Mohammad, H; Yaman, S K
Abstract: The construction industry is a very active and dynamic industry, which proceeding as one of the significant industry that contributing to the country's economy. Unfortunately, the construction industry has also earned the reputation of being the riskiest industry because of the higher rates of accidents and fatalities. Nevertheless, overwhelming focus by many on the accident in the workplace has shaded the alarming issue of the construction-related commuting accident. As reported by the Malaysia's Social Security Organisation (SOCSO) in 2016, the number of commuting accidents and the compensations paid is increasing each year, and it is including the construction sector. Aware of the importance of safe commuting, several Malaysian agencies have developed their guidelines specifically for the improvement of such issue. Regrettably, the number of guidelines published does not exemplify the improvement of such issue when the number of commuting accidents is on the rise, especially for the construction sector. Therefore, this preliminary research was conducted to identify the safe commuting factors from the existing guidelines through manual document analysis. The finding shows that there are four (4) major categories namely; (1) driver/human factor, (2) vehicle factor, (3) environment factor, and (4) others. Hence, the research posits for subsequent exploration to ensure strategic implementation of those factors that will benefit the Malaysia's construction sector.